Unraveling the antecedents of Internet gaming disorder and mind-wandering as an outcome in MOBA youth players - Soo, Ting T’ng; Ho, Khee Hoong; Leong, Wen Sam; Siah, Poh Chua; Hon, Kai Yee; Nurul Iman Abdul Jalil (Informa UK Limited, 2025)
The exponentially growing game genre - multiplayer online battle arena (MOBA) is propelled into the gaming culture. Employing the Interaction-Person-Affect-Cognition-Execution (I-PACE) model, this study examines the (1) predictive effects of impulsivity on IGD; (2) IGD on mind-wandering, (3) simple mediating effects of in-game satisfaction and self-control on impulsivity and IGD respectively, (4) sequential mediating effects (i.e., self-control, in-game satisfaction, IGD) on impulsivity and mind-wandering. 710 youth are included in the final analyses of this cross-sectional online survey study. The findings show that impulsivity predicts IGD positively. IGD is also a positive predictor of mind-wandering. In the simple mediation analyses, in-game satisfaction is not a significant mediator, whereas self-control is a significant mediator for impulsivity and IGD. Both self-control and in-game satisfaction sequentially mediate impulsivity and IGD. Lastly, the indirect effect between impulsivity and mind-wandering with three sequential mediators (i.e., self-control, in-game satisfaction, and IGD) is significant. A total of 41.9% variances of IGD (a large R2 effect size) and 22.2% variances of mind-wandering (a moderate R2 effect size) were explained. Future prevention and intervention should highlight the importance of individuals being empowered to navigate the gaming environment with a well-balanced and resilient mindset, fostering a healthier connection with online gaming.